Pedagogical Strategies of Secondary Social Studies Classroom from Teachers’ Perspectives (Siddhajyoti Interdisciplinary Journal, 2026)
This study examines the implementation of diverse pedagogical strategies by secondary-level Social Studies teachers to actively engage students, achieve curriculum objectives, and address the needs of learners from varied cultural and social backgrounds. Using a qualitative phenomenological approach, the research centers on the lived experiences of four teachers, two from rural schools and two from urban schools through interviews and classroom observations. Findings reveal that teachers integrate student-centered, behaviorist, and cognitive approaches in their instruction. Group discussions, reflective activities, and real-life examples are employed to foster critical thinking, problem-solving, and responsible civic behavior. Lessons are further enriched through local cultural and historical references, enhancing the relevance and meaning of the content for students. Despite challenges such as overcrowded classrooms, limited teaching resources, insufficient ICT facilities, and syllabus pressures, teachers demonstrate creativity, commitment, and reflective practice to promote active learning and civic awareness. The study highlights the importance of practical teaching strategies, adequate resources, and professional development opportunities in strengthening Social Studies education, ultimately supporting the cultivation of informed, responsible, and engaged citizens in Nepal.